2012
DOI: 10.1136/emermed-2012-201139
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric consultation service in emergency department: how does it work?

Abstract: Programme 'We Care' provided comprehensive geriatric assessment to suitable geriatric patients, resulting in an effective reduction of acute geriatric hospital admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Research about CGA at the ED is scarce and considerable heterogeneity is observed between reported interventions. Descriptive research has demonstrated the feasibility of CGA interventions, and documented a large range of undetected care needs [ 31 - 34 ]. To the authors’ knowledge only three randomized controlled trials [ 35 - 37 ] and two pre-post implementation studies [ 29 , 38 ] reported outcomes of a geriatric intervention at the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Research about CGA at the ED is scarce and considerable heterogeneity is observed between reported interventions. Descriptive research has demonstrated the feasibility of CGA interventions, and documented a large range of undetected care needs [ 31 - 34 ]. To the authors’ knowledge only three randomized controlled trials [ 35 - 37 ] and two pre-post implementation studies [ 29 , 38 ] reported outcomes of a geriatric intervention at the ED.…”
Section: Discussionmentioning
confidence: 99%
“…37 When possible, previously validated survey instruments are preferable, 38 but for our objectives, no such instrument exists. Therefore, our survey instrument was developed by a detailed review of existing research focused on ED interventions to improve geriatric adult emergency care, 5,6,13,15,20,25,26,32,34,35,[39][40][41][42][43][44][45][46] as well as discussions with a multidisciplinary collaboration of representatives from SAEM, ACEP, the American Geriatrics Society, and the Emergency Nurses Association. This collaboration continues to develop geriatric ED infrastructure, personnel, protocol, and educational guidelines.…”
Section: Survey Content and Administrationmentioning
confidence: 99%
“…The national multispecialty Geriatric ED Guidelines recognize this problem and endorse Multidisciplinary Geriatric Assessment for all high-risk ED patients [11]. Multidisciplinary assessment by geriatricians, case managers, pharmacists, and physical therapists (PTs) in the ED can identify geriatric syndromes and address needs, which leads to decreased unnecessary hospitalizations [12][13][14][15][16][17][18]. Studies of multidisciplinary assessment in the ED show measurable benefits with decreases in hospitalizations, intensive care unit admissions, ED revisits, and functional decline at 6 months [12,15,17,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Multidisciplinary assessment by geriatricians, case managers, pharmacists, and physical therapists (PTs) in the ED can identify geriatric syndromes and address needs, which leads to decreased unnecessary hospitalizations [ 12 18 ]. Studies of multidisciplinary assessment in the ED show measurable benefits with decreases in hospitalizations, intensive care unit admissions, ED revisits, and functional decline at 6 months [ 12 , 15 , 17 , 19 24 ].…”
Section: Introductionmentioning
confidence: 99%